Implementação de Difusão Atômica Baseada em Diagnóstico com Testes Imperfeitos - de Camargo, Edson; Duarte Jr., Elias; Cassou-Pietniczka, Weyne (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
This paper describes two implementations of atomic broadcast, the first implementation is based on the Paxos consensus algorithm, while the other assumes a stable sequencer. The system is assumed to be composed of both unstable and stable processes. Stable processes are obtained and identified with a novel system-level diagnosis model which is based on imperfect tests. The performance of the strategy used to select stable nodes, as well as an experimental comparison of the two atomic broadcast strategies is shown though simulation.